Homogenous and multilayer electromagnetics models for estimating skin reflectance - Amani Yousef Owda; Majdi Owda (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Reflectance measurements of human skin are widely limited over the millimeter wave (MMW) band in literature. This is due to the cost and technical difficulties of the experimental setup. This paper proposes homogenous and multilayer skin models for estimating the reflectance of the forearm and palm of the hand skin over the MMW band 30-100 GHz. The simulation results demonstrate that the differences in reflectance between the homogenous and multilayer models of forearm skin are limited to 0.014, indicating that the thin stratum corneum (SC) layer in the multilayer skin models has a minimal impact on the interaction with MMW of the forearm skin. However, in the palm of hand skin, there is a substantial difference in reflectance calculations between the homogenous and the multilayer skin models in the range of 0.099 to 0.143. These differences are attributed to the presence of a thick SC layer in the palm of the hand. Thus, the simulation results suggested that two-layer should be used for the palm of hand skin as it better captures the reflectance characteristics of this region. The importance of having those models are in calculating the skin reflectance that can be used for the non-invasive diagnosis of skin conditions.